Evaluation of the e-BLUD-based Accounting System for Preparation of Financial Statements using the HOT-Fit Model Framework - Alya Ardianti Lahfah; Melati, Indah (E-Jurnal Akuntansi, 2026)
This study aims to evaluate the effectiveness of the e-BLUD (Electronic Regional Public Service Agency) system in preparing financial reports at Ahmad Ripin Regional General Hospital in Muaro Jambi Regency, based on the HOT-Fit model. This research is important because the implementation of BLUD financial digitization still faces challenges in systems, human resources, and technology integration to support accountability. The study used a qualitative case study approach. Data were collected through semi-structured interviews, observations, and documentation analysis, then analyzed thematically. The results indicate that e-BLUD improves work efficiency, reduces manual errors, and supports data-driven decision-making. Users demonstrated high acceptance, supported by an adequate organizational structure, although infrastructure constraints remain. This study contributes by providing a holistic HOT-Fit-based evaluation and recommendations for strengthening system and infrastructure integration to enhance the effectiveness of e-BLUD implementation.